(untitled) (Texas Journal of Medical Science, 2022)
Suicidal Behavior (SB) in adolescence is a growing concern. Suicide is the number one cause of death for adolescents, especially as they suffer from huge crises. The aim of this paper it was to evaluate the psychosocial risk factors for SB among adolescents in secondary school students in the city of Baghdad. The study used a cross section design and results in the primary analysis. Secondary school students aged 13-22 years were targeted. Four secondary schools were purposefully sampled and data were extracted from 300 respondents in all school students examined at baseline. Data were collected using the Suicidal Behavior Rating Scale for Adolescents (SENTIA), the Psychosocial Risk Factors Scale, and the Sociodemographic Questionnaire. The data analyzed using SPSS version 26 is presented in tables and the results are discussed. The results revealed psychological factors as significant risk factors (P < 0.001) for SB. Discrete logistic models established the following life stressors as psychosocial risk factors (p < 0.001) for SB in the next order of severity; Desperation and worthlessness, relationship problems, traumatic experiences, mental disorders, family problems, alcohol or drug abuse, physical illness, academic challenges, financial problems and the death of loved ones. The researcher concluded there are a number of factors that indicate a teenager commits suicide, as the family must pay attention to its children at this dangerous age, and monitor their behavior greatly for early detection of those at risk.